Dry Text Reception as Digital Body Language on WhatsApp: A Study of Meaning Interpretation Based on Stuart Hall’s Reception Theory - Zullaicha, Siti; Ronda, Mirza; Lusianawati, Hayu; Santoso, Prasetya Yoga (The Eastasouth Journal of Social Science and Humanities, 2025)
This study investigates the reception of “dry text” as a form of digital body language and the understanding of message meaning among WhatsApp users. In the evolving digital communication landscape, the absence of explicit non-verbal cues in text-based interactions, often referred to as “dry text,” presents unique challenges to message interpretation. Using a qualitative descriptive approach grounded in Stuart Hall’s Reception Theory, this study analyzes the nuanced understanding of message meaning, considering the interplay between context, relationship dynamics, and the individual’s psychological state. The study findings reveal that the interpretation of “dry text” is highly subjective and context-dependent, with factors such as relational intimacy, communication history, and current mood significantly influencing reception. While some users interpret “dry text” as efficient, others perceive it as negative, indifferent, or even rude. This study highlights the critical role of users’ communicative competence in navigating ambiguous digital cues and the potential for miscommunication when non-verbal signals are absent. This study contributes to a deeper understanding of digital body language and the complexity of meaning-making in text-based communication.